2009
DOI: 10.1093/aje/kwp095
|View full text |Cite
|
Sign up to set email alerts
|

Birth Weight, Postnatal Growth, and Age at Menarche

Abstract: Larger body size in childhood is correlated with earlier age at menarche; whether birth and infant body size changes are also associated with age at menarche is less clear. The authors contacted female participants enrolled in the New York site of the US National Collaborative Perinatal Project born between 1959 and 1963 (n = 262). This racially and ethnically diverse cohort (38% white, 40% African American, and 22% Puerto Rican) was used to investigate whether maternal (body size, pregnancy weight gain, age a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
105
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(120 citation statements)
references
References 43 publications
(77 reference statements)
13
105
2
Order By: Relevance
“…14 However, our findings differ from those of Terry et al 48 who did not find an association between maternal GWG and daughter's age at menarche in a similarly aged cohort of 262 women. The association between maternal GWG and age at menarche may operate through several pathways.…”
Section: Discussioncontrasting
confidence: 90%
“…14 However, our findings differ from those of Terry et al 48 who did not find an association between maternal GWG and daughter's age at menarche in a similarly aged cohort of 262 women. The association between maternal GWG and age at menarche may operate through several pathways.…”
Section: Discussioncontrasting
confidence: 90%
“…6 A study conducted by Terry MB et al in an ethnically and racially diverse cohort in US found that girls who weighed more with more body fat distribution at the age of 7 years attained earlier menarche. 20 This study also showed that girls who weighed lighter at birth had an earlier age of menarche, but no statistical significant correlation was observed. Our study also showed no significant relation between birth weight and age of menarche.…”
Section: Discussionmentioning
confidence: 57%
“…21 This result was in contrast to the study conducted in US. 20 In our study, most of the girls did not know their weight or height at the time of menarche and therefore the BMI at the time of menarche could not be calculated. Thus, we could not find out whether there was a correlation between age at menarche and BMI at menarche, this may be considered a limitation in our study.…”
Section: Discussionmentioning
confidence: 86%
“…Fledelius (1982) have suggested that in preterm-born girls and in girls with low birth weight (<2000 g), menarche occurs about 3-6 months later than in girls born at term. Similarly, Berankova (1997) have demonstrated that menarche was delayed by 3-6 months in girls with birth weight lower than 2500 g. Also Terry et al (2009) related low birth weight (<2500 g) to a higher probability of menarche at about 7.2 months later than in children with birth weight amounting to or greater than 2500 g.…”
Section: Discussionmentioning
confidence: 91%